Pengembangan Media Pembelajaran Pop-Up Book pada Pembelajaran IPAS Kelas IV di Sekolah Dasar - Sari, Dessy Rahma; Fatmawati, Risdiana Andika; Farisi, Salman Al (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to address the difficulties faced by fourth-grade students at SDN 41 Sungai Raya in understanding IPAS material due to the limited use of engaging learning media. A pop-up book learning media was developed with the goals of producing suitable media, practical media, and effective media for teaching IPAS. The research method used is Research and Development (R&D) with the ADDIE development model, which includes the stages of analyze, design, development, implementation, and evaluation. The product validation was conducted by three experts: media expert, subject matter expert, and language expert. Trials were carried out on fourth-grade students using questionnaires, pretests, and posttests. The validation results showed that the pop-up book media received a score of 88% from the media expert (highly suitable), 100% from the subject matter expert (highly suitable), and 66% from the language expert (suitable). Small group trials demonstrated a practicality score of 95% (highly practical) and effectiveness based on an N-gain score of 0.76 or 76% (effective). This pop-up book learning media is suitable, practical, and effective for teaching IPAS to fourth-grade students